Nereis and Platynereis (Polychaeta: Nereididae) from Victoria with description of a new species of Nereis - Wilson, R. S. (Proceedings of the Royal Society of Victoria, 1985)
Nereis apalie sp. nov. is described from Bass Strait. Nereis parabifida Hutchings & Turvey is synonomised with Nereis bifuda Hutchings & Turvey. A systematic account of Nereis known from Victoria and a key to species recorded from southern Australia is provided.
Nereis apaliae; Nereis bifida; Nereis cockburnensis; Nereis denhamensis; Nereis jacksoni; Nereis maxillodentata; Platynereis dumerilii antipoda; ; ; polychaete box, The following values have no corresponding Zotero field: alt-title: Proceedings of the Royal Society of Victoria label: RW Papyrus# 101240 custom1: RW checked
Keywords: CRIMP POLYCHAETES; POLYCHAETA NEREIDIDAE; RW_CV

Neanthes (Polychaeta: Nereididae) from Victoria with descriptions of two new species - Wilson, R. S. (Proceedings of the Royal Society of Victoria, 1984)
Two nereidid polychaetes are discribed from Victoria, Neanthes bassi sp. nov. and N. flindersi sp. nov. N. succinea Leuckart is recorded from Australia for the 1st time and the status of Nectoneanthes Imajima is discussed. A systematic account of Neanthes known from Victoria and a key to species recorded from southern Australia are provided. A list is appended of all species of Neanthes described to date.
Neanthes bassi; Neanthes biseriata; Neanthes cricognatha; Neanthes flindersi; Neanthes kerguelensis; Neanthes succinea; Neanthes uniseriata; Neanthes vaalii; ; ; polychaete box, The following values have no corresponding Zotero field: alt-title: Proceedings of the Royal Society of Victoria label: RW Papyrus# 101239 custom1: RW checked
Keywords: CRIMP POLYCHAETES; paragnath ms new; POLYCHAETA NEREIDIDAE; RW_CV